Early father-child and mother-child attachment relationships: contributions to preschoolers’ social competence - Fernandes, C.; Monteiro, L.; Santos, A. J.; Fernandes, M.; Antunes, M.; Vaughn, B. E.; Veríssimo, M. (Attachment and Human Development, 2020)
The main goal of this study was to explore the contributions of early father-child and mother-child attachment relationships to children’s later social competence with their preschool peers; possible unique and shared contributions were tested. Using a multi-method design and focusing on direct observation, attachment was assessed at home at age 3 with the Attachment Behavior Q-sort (AQS) and two years later social competence was assessed at classrooms of 5-year-olds using a set of seven measurement indicators that are part of the Hierarchical Model of Social Competence. Results show that attachment to each parent made unique and significant contributions to children’s social competence and suggested the possibility that each caregiver may have somewhat different patterns of influence on the different indicators of children’s social competence. Findings also suggest the possibility that a secure attachment with one parent may buffer the impact of having an insecure relationship with the other. Due to sample size these results should be seen as a starting point to generate new and larger studies.